PENINGKATAN KEMAMPUAN PENGELASAN SMAW POSISI 2F PEMUDA KELURAHAN KOTO LUAR KECAMATAN PAUH PADANG - Yuli Yetri; Zulhendri; Yuliarman; Yasmendra Rosa; Rino Sukma; Junaidi; Yusri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2019)
The community service program carried out by the Mechanical Engineering Department, Padang State Polytechnic lecturer is an activity in order to fulfill the Tridarma of Higher Education for the 2018 budget year. The activity was held in the form of SMAW 2F welding improvement training for the youth of Koto Luar, Pauh sub-district, Padang. In this area, there are many high school graduates who have not dared to enter the real workforce because they feel they do not have sufficient skills to join the field workforce. On the other hand, the Koto Luar village is currently developing very fast, because there has been assimilation between migrants and indigenous people. Along with increasing population, of course also followed by the addition of living facilities. To synergize the increase in progress with its human resource capabilities, various knowledge and skills are needed, one of which is the electric welding skills knowledge of SMAW 2F. Its welding training was attended by 21 Koto Luar youths for 4 days at the Mechanical Engineering department workshop. Expected abilities after training, Koto Luar youths are able to properly weld 2F methods according to welding standards, so that later participants are expected to enter the world of welding work. After debriefing the participants can take part in the welding training well, so that they get the SMAW 2F welding certificate signed by the director of the Padang State Polytechnic. The welding enhancement training activity of SMAW 2F received positive support from the chairman of the Community Empowerment Agency (BPM) and village leaders, because this activity had long been wanted by the community. The Koto Luar community hopes that the training to improve SMAW 2F's welding ability for youth in Pauh Padang sub-district can be carried out continuously, because many young people are interested in SMAW's welding knowledge, the goal is to be able to open entrepreneurs and fill jobs around Lambung Bukit, Koto Luar , and Limau Manis Padang.